El problema del análisis de las discusiones asincrónicas en el aprendizaje colaborativo mediado. - Begoña Gros; Juan Silva (Universidad de Murcia, 2006)
In this article we analyse the state of the art about the research methodologies used to analysis of computer supported communication. We will describe and discuss the main proposals about qualitative analysis of the interventions. Current studies are focus on the used of pre-categorization based on specific models, and other methodologies based on inductive approaches. Finally, we will analyses methodologies to study the conditions of collaborative learning based focus on the intervention of the participants.